2022
DOI: 10.3390/electronics11203294
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a UWB Positioning System Applied to Static and Mobile Use Cases in Industrial Scenarios

Abstract: Indoor positioning systems are essential in the industrial domain for optimized production and safe operation of mobile elements, such as mobile robots, especially in the presence of static machinery and human operators. In this paper, we assess the performance of a commercial UWB radio-based positioning system deployed in a realistic industrial scenario, considering both static and mobile use cases. Our goal is to characterize the accuracy of this system in the context of industrial use cases and applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…In comparison to our previous study, reported in [15], where the UWB deployment in the same industrial operational scenario considered only 8 infrastructure anchors (half than in this study), the UWB positioning performance have now improved. While the median accuracy performance is similar, the maximum ranging error is reduced by a factor of 2.…”
Section: ) Performance In Static Conditionscontrasting
confidence: 40%
See 1 more Smart Citation
“…In comparison to our previous study, reported in [15], where the UWB deployment in the same industrial operational scenario considered only 8 infrastructure anchors (half than in this study), the UWB positioning performance have now improved. While the median accuracy performance is similar, the maximum ranging error is reduced by a factor of 2.…”
Section: ) Performance In Static Conditionscontrasting
confidence: 40%
“…Among the numerous indoor RTLS technologies that rely on radio frequency (RF) signal exchange, such as Wi-Fi, Bluetooth, Infrared, and RFID; UWB stands out due to its exceptional combination of accuracy, reliability, scalability, realtime tracking capabilities, and low power consumption [13], [14]. These attributes have made of UWB a preferred choice for an efficient location tracking solution in industrial settings, achieving an operational accuracy in the range of 20 cm to over 100 cm, depending on the factory conditions [15].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, the AMRs are configured to self-navigate the industrial lab, following predefined routes and missions. This fact, initially designed to maximize the performance in industrial processes involving mobile robots [27], simplifies the radio propagation analysis by automating the measurement process, ensuring route repeatability with cmlevel accuracy. Thus, the RSRP can be acquired given the different locations of the AMR in the factory.…”
Section: B 5g Nr Physical Channel and Measurement Equipmentmentioning
confidence: 99%
“…Multiple technologies have been proposed in the past to perform indoor localization, many of which have demonstrated good localization performance for different use cases. Regarding this study, multiple articles [26][27][28][29], aim to compare technologies such as RFID, Ultrasonic Sensors, Bluetooth Low Energy, Ultra-Wide-band, and Wi-Fi in order to identify occupancy patterns and profiles in indoor spaces. The basic specifications of some indoor positioning technologies are presented in Table 1.…”
Section: Related Workmentioning
confidence: 99%